Elucidating the path to Plasmodium prolyl-tRNA synthetase inhibitors that overcome halofuginone resistance - Mark A. Tye; N. Connor Payne; Catrine Johansson; Kritika Singh; Sofia A. Santos; Lọla Fagbami; Akansha Pant; Kayla Sylvester; Madeline R. Luth; Sofia Marques; Malcolm Whitman; Maria M. Mota; et al. (Nature Communications, 2022)
The development of antimalarials against the human liver and asexual blood stages is one of the top public health challenges. Here, the authors report a single-step biochemical assay for the characterization of prolyl-tRNA synthetase inhibitors, and develop high-affinity inhibitors for the enzyme, including elusive triple-site ligands.